Sex Education Transformation: Efforts to Grow Moral in Islamic Views in Early Childhood in the Family - Dalmeri Dalmeri; Muhamad Parhan; Erlina Annisa Faujiah; Putri Faza Aulia Az-Zahra; Rosdiana Nur Fauziah; Syarifah Nur Amanah (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
The fast-moving conditions and development of the times and the easy access to mass media at every level requires that parents provide their children with an education. The education aimed at is sex education for children of an early age. The increasing problem of sexual deviancy behavior in Indonesia is that one is the result of a lack of understanding about sexual education. Sex education should be applied early to have good morals and not be prone to promiscuity. Premature age is a golden phase for children, treatment of them can affect their life into adulthood. The research aims to learn the importance of sexual education in an early-age child's morals based on Islamic religious views. A research approach uses a qualitative approach for case study methods. Studies reveal sexual education should be given concurrently with a religious basis. Child sexual education needs to be implemented by family members as protection for their children.